Preparing the Future STEM Workforce for Diverse Environments. (September 2013) - Daily, Shaundra Bryant; Eugene, Wanda
Following the belief that diversity breeds innovation in scientific endeavors, there is a national push for more diversity in the science, technology, engineering, and mathematics (STEM) workforce in order to maintain national economic competitiveness. Currently, STEM-related employment is only 28% non-White; however, greater efforts to recruit and retain underrepresented minorities should increase this figure. Amidst the attention given to supporting "leaky pipelines, " less emphasis has been placed on mitigating challenges associated with bringing diverse cultures together. This article presents a framework for supporting underrepresented minorities in building STEM-relevant skills and enhancing their ability to collaborate with peers different from themselves.